The aging body in dance a cross-cultural study - Brandstetter, Gabriele; Nakajima, Nanako (New York : Routledge, Taylor & Francis Group, 2017)
The Aging Body in Dance brings together leading scholars and artists from a range of backgrounds to investigate cultural ideas of movement and beauty, expressiveness and agility. Contributors focus on Euro-American and Japanese attitudes towards aging and performance, including studies of choreographers, dancers and directors from Yvonne Rainer, Martha Graham, Anna Halprin and Roemeo Castellucci to Kazuo Ohno and Kikuo Tomoeda. They draw a fascinating comparison between youth-oriented Western cultures and dance cultures like Japan's, where aging performers are celebrated as part of the country's living heritage. The first cross-cultural study of its kind, The Aging Body in Dance offers a vital resource for scholars and practitioners interested in global dance cultures and their differing responses to the world's aging population.